Influence of Strategic Responses on Project Performance of the Telecommunication Sector: A Case of Telkom Kenya Limited, Nairobi County - Kimani, George Kinyanjui; Omutoko, Dr. Lilian (International Journal of Entrepreneurship and Project Management, 2016)
Purpose: Globalization and the global dynamics of the market are forcing many enterprises, including the telecommunications industry, to develop new strategies. The trends and the dynamic development in the telecommunications market are the starting points for a company's sourcing strategy and they form the framework for action. The purpose of this study was therefore to determine the influence of strategic responses on project performance in the telecommunication sector. Methodology: The target population was composed all employees of TKL as contained in the personnel register as at 31st January 2015. These are a total of 3000 employees but the study only targeted a population of the 300 management staff. Data collected from the questionnaires was converted from responses to quantitative format for ease in analysis using statistical package for social sciences (SPSS Version 20). Results: Strategic pricing, sstrategic human resource training, strategic lobbying and strategic product development were all found to be positively and significantly related to project performance. Unique contribution to theory, practice and policy: The study recommended that Project managers should focus more of their effort on strategic pricing strategy because there was a significant level of effect of penetration pricing strategy on the number of customers, customer loyalty and quality of service, creating and implementing policies and human resource development practices which can ensure their contribution to acquiring the organizational goals.